A case study analysis of racial identity in heterosexual black and white interracial couples living in the south - Osby Williams, Jamie Leigh (Kansas State University, 2009)
There has been a rapid growth of heterosexual Black and White interracial couples in the United States in recent decades and numbers continue to increase. In addition, the concept of racial identity within Southern heterosexual Black and White interracial couples has not been explored. The purpose of this qualitative study was to understand how racial identity affects the dynamics of Black and White interracial relationships within the context of their extended family and community and the effect of interracial relationships on racial identity development. The focus of the study was to explore how partners in heterosexual Black and White interracial couples living in the South constructed and/or defined their individual racial identity, how the couple addressed cultural difference within the relationship, and how the couple handled opposition toward their relationship. Three theoretical/philosophical frameworks were used in this study. Phenomenology and social constructionism were utilized to provide a framework for the methodology of the study; Black racial identity theory (Cross, 1971, 1991) and White racial identity theory (Helms, 1990) were utilized to provide a framework for thinking about racial identity development. The sample consisted of four couples, each with children. Each couple was interviewed conjointly in a neutral setting and then allowed the researcher to accompany them on an outing in a public setting. This experience allowed the researcher to observe how the couple was received in public and how the couple managed public response. Interviews provided rich descriptions of how the research participants experienced themselves as individuals and as a couple in their marriage with respect to racial identity. Through case study analysis, six main themes and 22 sub-themes were identified. The main themes included: marital dynamics, racial identity, influences, reactions, advice, and counseling. Cross-case analysis revealed a small number of subthemes shared across cases. Differences between cases were considerable and were presented via the identification of new subthemes and unique cases. Three new subthemes were identified: normal couple, gaining acceptance, and religious affiliation. Recommendations are offered for future research and, tentatively, for marriage and family therapists who may work with couples similar to those in this study. Most notably, couples in this study saw themselves as “normal couples” brought together by love, and did not necessarily think of themselves as “interracial.” They did, however, talk as a couple about how to racially identify their children and how to help them respond to questions about their racial heritage.
Keywords: Black and White interracial couples; Racial identity; Racial identity development; interracial couples; Sociology, Individual and Family Studies (0628)